The impact of corporate governance on the social and environmental information disclosure of Malaysian listed banks: panel data analysis - Htay, Sheila Nu Nu; Ab Rashid, Hafiz-Majdi; Adnan, Muhammad Akhyar; Mydin Meera, Ahamed Kameel (2011)
This study investigates the impact of corporate governance on social and environmental information disclosure of Malaysian listed banks by using a panel data analysis. Good corporate governance is proxied by board leadership structure, board composition, board size, director ownership, institutional ownership and block ownership. Social and environmental information disclosure index is developed and content analysis is conducted by cross checking between the social and environmental information disclosed in the annual reports and the disclosure index developed by the researcher. The disclosure score used in this study is weighted disclosure score after considering the opinions of accountants and financial analysts who represent preparers and users of the accounting information respectively. The findings show that smaller board size, higher percentage of independent directors (1%) on the board, higher board size (1%), higher percentage of director ownership, lower institutional and lower block ownership (5%) have higher information disclosure.